Senyawa Turunan Organotimah: Sintesis dan Struktur Kristal Trifeniltimah Pentasiano Propenida [(C6H5)3Sn][C3(CN)5] 2H2O - Asrial Asrial; Frank T. Edelmann (Jurnal Matematika & Sains, 2010)
Triphenyltin-1,1,2,3,3-pentacyano prophenide compound, [(C6H5)3Sn][C3(CN)5]2H2O, is the stable organometallic complex, which is a macromolecule compound. This compound is synthesized from triphenyltin chloride, (C6H5)3SnCl, and silver pentacyano prophenide, AgC8N5, in tetrahydrofuran (THF). This compound has crystal system of monoclinic with space groups of P2(1)/n with a = 825.37(10); b = 2092.91(03); c = 1484.07(10) pm, a = g = 90,00Â° and b =103.84(10)o; and cell volume = 2.49(05) nm3. The compound consists of [C3(CN)5]- anion and [(C6H5)3]+ cation in slightly different packing modes.